Contemplating and Proclaiming the Meaning of Christmas: A Biblical Hermeneutical Study on the Incarnation of Christ and Its Implications for the Life of Believers - Mawikere, Marde Christian Stenly; Hura, Sudiria (LIMMUD: Jurnal Ilmu Keagamaan dan Sosial Humaniora, 2024)
This study examines the meaning of Christmas from a biblical perspective and explores how its values can be lived out and proclaimed daily by believers. Christmas is often observed as an annual tradition without a profound understanding of the incarnation of Christ and the fulfilment of God's promise of salvation. The research employs biblical hermeneutics, utilising an expository approach and thematic analysis of Old and New Testament texts. The findings reveal that Christmas affirms Jesus as the HaMoshia (Saviour), reflects the paradox of the Kingdom of God, and serves as a call to proclaim the Gospel. In conclusion, Christmas is not merely an annual celebration but a summons to live in the light of Christ and to proclaim the message of salvation to the world each day.